Roberta Gilchrist: Medieval Life. Archaeology and the Life Course - Clark, Letitia (Petits Propos Culinaires, 2013)
Roberta Gilchrist: Medieval Life. Archaeology and the Life Course: The Boydell Press, 2012, 336 pp., hardback, £30.00.